Causes & Effects of Financial Exclusion in the Banking Sector: the case of Zimbabwe - Wilson Nyarugwe; Gabriel Maibvisira; Florence Mudzurandende (International Journals Of Multidisciplinary Research Academy, 2022)
The study sought to establish causes and effects of financial exclusion in Zimbabwe from 2009 to 2011 . The study adopted both descriptive and exploratory research designs owing to the qualitative and insightful nature of the study . A diverse sample of 200 comprising bank managers , the unbanked population , bank clients and officials from the Central Bank was used and the sample was drawn from the three delimited towns. Structured and semi- structured questionnaires, in-depth interviews and observation were used to gather data from the chosen sample . The study came out with fundamental findings inter –alia ; the majority of the unbanked population were in the informal sector , the rural and the low income population, the crisis of 2003 -2008 eroded people‟s confidence in banks resulting in self exclusion, financial exclusion impacted negatively on the economy as a result of liquidity crunch and an estimated US $ 2.5 billion is circulating outside the formal banking system thereby reducing the country to a “cash economy,” and the majority of the unbanked are the general population and the small to medium enterprises who cannot meet the stringent bank loans requirements. Major recommendations are ; the need for banks to increase frequency of their mobile banking units to the marginalized unbanked in rural areas , banks to revise their bank charges so as to attract and retain depositors, banks to practice sound corporate governance and business ethics to regain depositors confidence .